Eventmanagement in de praktijk : eventcases en andere praktijkvoorbeelden - Verhaar, Jan, 1949-; Rosman, Cees, ....- (Den Haag : Eleven international publishing, 2011)
Events have become of increasing significance, both from a communicative, cultural and even tourist valuepoint of view. Just think about the large number of events that is organized annually by and within cities and neighborhoods. As a result, a new phenomenon appeared: city marketing. The rise of social media is unstoppable, especially around events. Moreover, in addition to concept development, the 2010 Love Parade disaster in Duisburg has led to special attention to security during events. This book is primarily meant for college teachers and students of Media and Entertainment Management, Event Management, and students from similar fields such as Sports Management and Hotel Management. It is of importance for professionals in these fields as well as for international programs in similar areas.